2018
DOI: 10.3389/fendo.2018.00646
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Bone Mineral Density, Bone Turnover Markers, and Serum Cholesterol Levels in Type 2 Diabetes

Abstract: Purpose: The association between bone mineral density (BMD), bone turnover markers, and serum cholesterol in healthy population has already been proved. However, in patients with type 2 diabetes mellitus (T2D), it has not been adequately analyzed. In this study, we investigated the correlation between BMD, bone turnover markers, and serum cholesterol levels in people with T2D.Methods: We enrolled 1,040 men and 735 women with T2D from Zhongshan Hospital between October 2009 and January 2013. Their general condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Epidemiological and clinical research revealed constructive outcomes of isoflavone utilization over bone with the danger of building up a few osteoporosis. (6) This study aims to examine the impact of Red clover oil on bone healing in rats histomorphometrically.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical research revealed constructive outcomes of isoflavone utilization over bone with the danger of building up a few osteoporosis. (6) This study aims to examine the impact of Red clover oil on bone healing in rats histomorphometrically.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between blood lipid metabolism and bone mineral density has been widely studied in the general population; there are some potential mechanisms of serum lipid on bone metabolism. Oxysterols should be removed by HDL-C from peripheral tissues, and osteoblasts' differentiation is inhibited by LDL oxidation products, so cholesterol, HDL-C, and LDL-C can direct progenitor MSCs (mesenchymal stem cells) to undergo lipogenic instead of osteogenic differentiation and induce RANKL-(receptor activator of nuclear factor-kB ligand-) dependent osteoclastic differentiation, and our results also showed their negative effects on osteogenic differentiation [11,12]. Trimpou et al [13] observed necrosis of the femoral head under an electron microscope and found that the number and size of fat cells increased significantly, indicating that lipid metabolism may play an important role in the formation of bone geometry.…”
Section: Discussionmentioning
confidence: 51%
“…Numerous studies investigated the association between cholesterol and BMD in the general population, but conclusions were inconsistent. In most studies, a higher level of cholesterol was found to be associated with an increased risk of osteoporosis or a lower BMD ( 5 8 ). A non-association between cholesterol and BMD was also reported ( 9 11 ).…”
Section: Discussionmentioning
confidence: 99%